Zircon xenocrysts from cenozoic alkaline basalts of the ratanakiri volcanic province (Cambodia), southeast asia—trace element geochemistry, O-Hf isotopic composition, U-PB and (U-TH)/he geochronology—revelations into the underlying lithospheric mantle - Piilonen, P.C.; Sutherland, F.L.; Danišík, M.; Poirier, G.; Valley, J.W.; Rowe, R. (MDPI, 2018)
Zircon xenocrysts from alkali basalts in Ratanakiri Province, Cambodia represent a unique low-Hf zircon within a 12,000 km long Indo-Pacific megacryst zone. Colorless, yellow, brown, and red crystals ({100}, {101}, subordinate {211}, {1103}), with hopper growth and corrosion features range up to 20 cm in size. Zircon chemistry indicates juvenile, Zr-saturated, mantle-derived alkaline melt (Hf 0.6–0.7 wt %, Y <0.2 wt %, U + Th + REE (Rare-Earth Elements) < 600 ppm, Zr/Hf 66–92, Eu/Eu*N ~1, positive Ce/Ce*N, HREE (Heavy REE) enrichment). Incompatible element depletion with increasing Yb/SmN from core to rim at ~ constant Hf suggests single stage growth. Ti-in-zircon temperatures (~570–740 _C) are lower than predicted by crystal morphology (800–900 _C) and decrease from core to rim (DT = 10–50 _C). The _18O values (4.88 to 5.01‰ VSMOW (Vienna Standard Mean Ocean Water)) are relatively low for xenocrysts from the zircon Indo-Pacific zone (ZIP). The176Hf/177Hf values (+εHf 4.5–10.2) give TDepleted Mantle model source ages of 260–462 Ma and TCrustal ages of 391–754 ma. The source magmas reflect variably depleted lithospheric mantle with little supracrustal input. Zircon U-Pb (0.88–1.56 Ma) and (U-Th)/He (0.86–1.02 Ma) ages are older than host basalt ages (~0.7 Ma), which suggests limited residence before transport. Zircon genesis suggests Zr-saturated, Al-undersaturated, carbonatitic-influenced, low-degree partial melting (<1%) of peridotitic mantle at ~60 km beneath the Indochina terrane.